Sampling protocol to assess occupational exposure to bioburden in clinical facilities - Viegas, Carla (2019)
FCT – Project EXPOsE – Establishing protocols to assess occupational exposure to microbiota in clinical settings (02/SAICT/2016 – Project nº 23222).